INTEGRASI SPIRITUALISME DALAM PEMBELAJARAN BERBASIS DIGITAL DI ERA REVOLUSI 5.0 - Dasuki, Moh. (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2024)
The Fifth Industrial Revolution promotes a human-centered approach to education by integrating technology with spiritual and emotional development. Learning should address both cognitive and inner well-being aspects. This study employed a descriptive qualitative design using content analysis. Data were sourced from TikTok and Instagram by analyzing posts tagged with #SpiritualLearning and #SpiritualAwakening. Spiritual-themed content—such as from @philgoodlife—offered emotional support, motivation, and spiritual guidance to students. These positively influenced their spiritual well-being, learning motivation, and academic outcomes. The findings highlight that integrating spirituality in digital learning is not only relevant but essential in cultivating intellectually and spiritually balanced learners. This supports the shift toward holistic education in the digital age. Revolusi Industri 5.0 menekankan integrasi teknologi dan nilai-nilai kemanusiaan, termasuk spiritualitas dalam pendidikan digital. Pembelajaran tidak hanya menuntut aspek kognitif, tetapi juga keseimbangan emosional dan spiritual peserta didik. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik analisis konten. Data dikumpulkan dari platform TikTok dan Instagram melalui pemantauan tagar seperti #SpiritualLearning dan #SpiritualAwakening. Konten digital bertema spiritual—seperti dari akun @philgoodlife—memberikan inspirasi, motivasi, dan panduan emosional bagi siswa. Hal ini berdampak positif terhadap kesejahteraan spiritual, motivasi belajar, dan pencapaian akademik. Hasil menunjukkan bahwa pembelajaran digital berbasis spiritual bukan hanya relevan, tetapi juga strategis dalam membentuk generasi yang seimbang secara intelektual dan spiritual. Integrasi ini mencerminkan kebutuhan akan pendekatan holistik dalam pendidikan abad ke-21.